The Vendor Business School: Strengthening informal urban food businesses and the supply of healthy food in Quezon City, Philippines - Roa, Julieta; Bertuso, Arma; Ricarte, Phoebe; Prain, Gordon (CGIAR System Organization, 2024)
This policy brief highlights the opportunity to increase efficiency and safety of city food systems by developing the capacity of informal sector food vendors in the Philippines, a country with about 54 percent of the people living in urban and peri-urban areas (PSA 2022).